Determinants of high- and low- ability in mathematics - Labasan, Jocelyn A. (2006)
This study aimed to identify factors from home background variables, personal attributes, and intermediary factors that differentiate high and low ability students in Mathematics. The study used quantitative research design and collected data through eight locally validated questionnaires. The plan was implemented on 129 high-ability and 129 low-ability students from three national high schools in Nueva Vizcaya. It was concluded that there is a significant relationship between home background variables and students' attitude towards Mathematics. The researcher recommended among others that the Teacher Education Institutes (TEI) integrate the findings in the new preservice education for mathematics and School administrators in coordination with the the guidance counselors and advisers must disseminate information to parents.